Clinical significance of integrin αV and β superfamily members and focal adhesion kinase activity in oral squamous cell carcinoma: a retrospective observational study - Shigeru Sakurai; Yasutaka Ishida; Tomoaki Shintani; Sachiko Yamasaki; Kensaku Matsui; Tomoaki Hamana; Tadayoshi Nobumoto; Souichi Yanamoto; Yasutaka Hayashido (Frontiers Media S.A., 2024)
Objectives: Integrins are heterodimeric transmembrane plasma membrane proteins composed of α- and β-chains. They bind to extracellular matrix (ECM) and cytoskeletal proteins as ECM protein receptors. Upon ECM protein binding, integrins activate focal adhesion kinase (FAK) and transduce various signals. Despite their importance, integrin and FAK expression in oral squamous cell carcinoma (OSCC) tissue and the prognosis of patients with OSCC remains elusive.Methods: In a retrospective observational study, we immunohistochemically evaluated integrin αV, β1, β3, β5, β6, FAK, and phosphorylated-FAK (pFAK) expressions as prognostic predictors in 96 patients with OSCC. Patients were classified as positive or negative based on staining intensity, and clinicopathologic characteristics and survival rates of the two groups were compared. The association between above integrin-related proteins and PD-1 or PD-L1 in OSCC tissues was investigated.Results: We observed immunohistochemical integrin αV, β1, β6, β8, and FAK expressions in the cell membrane and cytoplasm but not integrin β3 and β5 in the OSCC tissues. pFAK was expressed in the cytoplasm of OSCC cells. The overall survival rate significantly decreased in pFAK-positive OSCC patients compared to the negative group, and cervical lymph node metastasis significantly increased in integrin β8-positive patients with OSCC (p < 0.05). No association between integrin-related proteins and PD-1 or PD-L1 in OSCC tissues was observed.Conclusion: Our results indicate that pFAK and integrin β8 are prognostic factors for OSCC. Therefore, pFAK- and integrin β8-targeting new oral cancer diagnostic and therapeutic methods hold a promising potential.